1996
DOI: 10.3109/00016489609137726
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 and TNF-α but no IL-2 Expression is Found in Squamous Cell Carcinomas of the Head and Neck by RT-PCR

Abstract: We studied the expression of IL-1 (Interleukin 1), IL-2, IL-4, IL-10, GM-CSF (granulocyte/macrophage colony stimulating factor), TNF-alpha (tumor necrosis factor alpha) and IFN-gamma (Interferon gamma) in tumor specimens and adjacent mucosa from 12 patients with squamous cell carcinoma of the head and neck (SCCHN) by reverse-transcribed polymerase chain reaction (RT-PCR). No IL-2 and IL-4 expression was detected in any of the tumor specimens. High level expression of IL-1 and TNF-alpha was found in all 12 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…PCR was performed as previously reported [10]. The amplified products were separated on a 1.5% agarose gel and stained with ethidium bromide, transferred to a positively charged nylon membrane (Boehringer Mannheim, Mannheim, Germany) and hybridized with a digoxigenin 3′ tailed internal oligonucleotide ( Table 1).…”
Section: Reverse Transcribed-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…PCR was performed as previously reported [10]. The amplified products were separated on a 1.5% agarose gel and stained with ethidium bromide, transferred to a positively charged nylon membrane (Boehringer Mannheim, Mannheim, Germany) and hybridized with a digoxigenin 3′ tailed internal oligonucleotide ( Table 1).…”
Section: Reverse Transcribed-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…One microgram of total RNA was used as template for first-strand cDNA synthesis with an oligo-dT primer (RT-PCR kit, Perkin Elmer, Foster City, Calif., USA), as described previously [8]. Approximately 10% of the cDNA reaction was subjected to a polymerase chain reaction (PCR) using the specific IL-1α primers 5′-GCCAATGACTCAGAGGAAGA and 3′-TCTCAGGCATCTC-CTTCAGC, resulting in a 353 bp product.…”
Section: Isolation Of Mrna and Cdna Synthesismentioning
confidence: 99%
“…It has recently been reported that IL-1α is produced in many human cancer cell lines, including those of bladder cancer [3], thyroid carcinoma [4,5], gastric carcinoma [6], ovarian cancer [7], squamous cell carcinoma [8][9][10], and pancreatic carcinoma [11]. We have revealed that patients with tumors stained with IL-1 antibody by immunohistochemistry showed a higher incidence of liver metastasis of gastric cancers [12].…”
mentioning
confidence: 73%